fate of phosphorus of ash-rich biochars in a soil-plant system - Wang, Tao; Camps-Arbestain, Marta; Hedley, Mike (Plant and soil, 2014)
AIMS: The objectives were to investigate (i) the forms and release pattern of P from an ash-rich biochar-amended sandy soil; (ii) the transformation of biochar P in a soil-plant system. METHODS: Several methodologies (a bioassay test, soluble P extractions, a sequential P fractionation and successive P extractions via resin strips) were used to study the bioavailability and transformation of P in a sandy soil fertilised with either conventional P fertilisers [Ca(H₂PO₄)₂ (CaP) and Sechura phosphate rock (SPR)] or biochars produced from cattle manure (MAe) and alum-treated biosolids (BSe) at four temperatures (250, 350, 450, and 550 °C). RESULTS: Biochar P mainly contributed to increase soil resin-extractable P- and inorganic NaOH-extractable P-fractions, and thus to plant available P. The decrease in P concentrations of those fractions was caused by the uptake of P by plants rather than their transformations into more stable forms. P release rates diminished following the order: CaP > MAe > BSe > SPR, which indicates a decline in P availability from these P sources. CONCLUSIONS: Phosphorus-rich biochar can be used as a slow-release fertiliser. It is necessary to determine available P (either soil or fertiliser tests) in biochars prior to its application to soil, so that dose, frequency and timing of application are correctly established.